Educational philosophy in the French enlightenment from nature to second nature - Gill, Natasha (Farnham, Surrey, England ; Burlington, Vt. : Ashgate, 2010)
Natasha Gill offers the first comprehensive analysis of French educational thought before Rousseau. She situates Emile in the context of a pedagogical debate that had been under way for a century before its publication, reveals the importance of key transitional figures such as Etienne-Gabriel Morelly, and shows how French theorists came to see education as a vehicle through which individual liberation, social harmony and political unity could be achieved.
Locke's Educational Theory in Relation to his Philosophical and Political Thought -- The Natural External : Locke's Some Thoughts Concerning Education -- Locke : Father of Social Engineering or Champion of Liberty in Education? -- Sources of French Educational Thought and the Legacy of the Jesuits -- Childhood and Education in the Works of Claude Fleury, Charles Rollin, and Jean-Pierre de Crousaz -- "The Limits of Reform" and the Concept of Utility in Fleury, Rollin, Crousaz, and Mme de Lambert -- Educational Theory at Mid-century -- Morelly and Individual Education : Essai sur l'esprit humain -- Morelly and Social Education : Essai sur le coeur humain -- Morelly and the Politicization of Education -- The Scandal Over Helvetius's De l'Esprit and the Origins of the Helvetius-Rousseau Controversy -- Helvetius's De l'Esprit : The Argument for Full Equality -- Rousseau's Emile, Books I---III : Individual Education -- Emile, Books IV---V, and Emile et Sophie, ou les solitaires : Social and Moral Education -- The Expulsion of the Jesuits and the Educational Reformers of the 1760s -- The Influence of Educational-Philosophical Concepts on the Reform Plans of the 1760s -- Disciples and Critics : The Impact of French Enlightenment Educational Thought -- Appendix 1. Rousseau's Appropriation of Morelly -- Appendix 2. Helvetius's Critique of Rousseau's Educational Theory -- Appendix 3. Education in the Encyclopedie.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Education -- France -- History -- 17th century; Education -- France -- History -- 18th century; Education, Humanistic -- France -- History -- 17th century; Education, Humanistic -- France -- History -- 18th century; Education -- France -- Philosophy; Enlightenment -- France; Electronic books